Answer:
(2, - 1 )
Step-by-step explanation:
Given the 2 equations
2x - 5y = 9 → (1)
3x + 4y = 2 → (2)
Multiplying (1) by 4 and (2) by 5 and adding the result will eliminate the y- term
8x - 20y = 36 → (3)
15x + 20y = 10 → (4)
Add (3) and (4) term by term to eliminate y
23x + 0 = 46
23x = 46 ( divide both sides by 23 )
x = 2
Substitute x = 2 into either of the 2 equations and solve for y
Substituting into (2)
3(2) + 4y = 2
6 + 4y = 2 ( subtract 6 from both sides )
4y = - 4 ( divide both sides by 4 )
y = - 1
solution is (2, - 1 )